Vector Electronystagmography Analysis in Elderly Individuals with Dizziness Complaint - Ferreira,Lidiane Maria de Brito Macedo (2013)
Introduction  Vector electronystagmography is widely used to evaluate vestibular function; however, elderly patients may show changes not due to vestibular disorders. Aim  This study aims to characterize vector electronystagmography tests in the elderly participants in a service station of the Brazilian public health system, the Unified Health System (SUS) in the city of Natal, who presented with dizziness. Methods  A cross-sectional and clinical study to characterize the vector electronystagmography in 10 members of an elderly SUS referral center located in the city of Natal with dizziness. Results  Of 10 patients interviewed, 9 were women, and just 1 was a man. All complained of dizziness in the last year, and most of them had more than one type of dizziness. The main differential diagnosis was benign paroxysmal positional vertigo. Regarding vector electronystagmography, we found 20% of patients with semispontaneous nystagmus in at least one direction and changes in saccades latency in 100% of patients, with 20% in relation to the accuracy of pendular tracking changes at the frequency of 0.2 Hz, 10% at 0.4 Hz, and 80% at 0.8 Hz, and 10% change in optokinetic gain. No patient had altered caloric test. Conclusion  Vector electronystagmography alterations in the elderly do not always indicate disease.